COMMUNICATION CONTROL SYSTEM OF ROBOT AII-SERIES WITH THE PERMANENT WELDING PROCESS SUPPORTING TOOL ON MOTORCYCLE FRAME BODY - Syahril Ardi; Desitia Utami (Technologic, 2012)
In order to meet the demand for the high quality and the minimal production cost, and then the manufacture company of the motorcycle was prosecuted to continue to carry out the innovation. One of the forms of his innovation was the development of process technology of welding permanent in frame body the motor. The process of welding automatically this used two robots welding and one robot handling. Besides this was gotten several supporting implements like: the security sensor, the sensor to operational, the operational switch, and the solenoid to move gripper & slider. In this research, was carried out by the design of the control system of integrated communication between the robot's three units with his supporting implement that could control as well as visualize the process of welding. This control system was carried out manually or automatically, by considering the aspect of the safety of the operator and the machine. As controller especially, this system used Programmable Logic Controller (PLC), Human Machine Interface (HMI) to monitoring the process that was taking place, and the system error recording. Automation of the process of permanent welding frame body this motor could go well. The process of welding frame body the motor could go in accordance with the function and the operation that were wanted. Results of welding (welding bead) are better and stable compared with welding manually, as well as could increase the security factor and the safety for the operator and the machine. Key word: System the control of communication, Programmable Logic Controller (PLC), Human Machine Interface (HMI)